PENGARUH MORFOLOGI PAYUDARA (PUTTING) TERHADAP KEBERHASILAN ASI EKSKLUSIF - Andrea Astuti, Windi; Widiyanti, Desi; Yuniarti; Destariyani, Elvi (JURNAL BESUREK JIDAN, 2024)
Exclusive breastfeeding is giving only breast milk for 6 months without additional food. Coverage of exclusive breastfeeding in Bengkulu Province in 2021 (68%), Bengkulu City (61.86%) but coverage of exclusive breastfeeding is still low in the Kampung Bali Community Health Center, Bengkulu City (19.1%). Factors that influence the success of breastfeeding are breast morphology (putting). The aim of the research is to breast morphology (putting) that influence the success of exclusive breastfeeding. The research design used a cross sectional approach for mothers with babies aged 6-12 months totaling 54 samples using the Lameshow formula, data were taken using purposive sampling techniques, data were analyzed univariately, bivariately and multivariately using the chi-square statistical test and logistic regression. . The research results showed that most (68.5%) mothers did not breastfeed exclusively, mothers had normal nipple shapes. There is a relationship between the initiation of breast morphology (putting) p value 0.043. It is hoped that future researchers will use qualitative methods with interviews to better understand what are the factors in the success of exclusive breastfeeding